Colour gamuts arising from absorber–dielectric–metal optical resonators. (22nd August 2017) - Oller, Declan; He, De; Kim, Jin Ho; Pacifici, Domenico; Xu, Jimmy; Fernandes, Gustavo E.
Abstract : Structural coloration is a quickly growing field, encompassing physical and photonic processes such as interference, diffraction, and scattering. In this study, we investigated the optical effects in the visible wavelength range, and in particular, the colour gamuts achievable with absorber–dielectric–metal sandwich structures. These chemical‐free layered structures are highly tunable, easily scaled, optical cavities that are capable of generating remarkable colours whose properties are determined completely by material and structural parameters. We employed experimental and numerical strategies to demonstrate that each absorber spans a unique colour gamut, i.e. a subset of the full chromaticity space. While gamut overlap is observed between different absorber types, the gamut areas unique to each absorber occur at different hues of high excitation purity. A comprehensive understanding of how these colour gamuts develop and how different materials may be combined to expand larger subsets of the chromaticity space is required in order to maximize the variety of colours achievable with this system and elevate it into a 'structural coloration technology'.